(untitled) (Práxis Educativa, 2024)
This article aimed to analyze the expansion of distance Higher Education at “Universidade Pitágoras Unopar” under the logic of financialization. The methodology adopted starts from the bibliographic survey, with a qualitative approach and documental analysis. The results show that “Universidade Pitágoras Unopar” has a large participation in Distance Learning in Brazil, representing approximately 12% among public and private Higher Education Institutions (HEIs), 13.41% among private HEIs in the year 2020. It was identified that the predominance of enrollments in the Distance Learning modality influenced Kroton/Cogna to create, in 2019 and 2020, eight colleges with the Unopar brand, in addition to creating marketing with digital platforms, with the objective of strengthening the Distance Learning market, showing that Higher Education via distance learning is expanding in a commodified way in the logic of the financialization of capital. Keywords: Financialization. Distance learning expansion. Unopar. Cogna/Kroton.